The buying and selling of identity in the 2024 presidential debate: A cultural politics approach to media and hegemony - Rasyad, Muhammad Ammar; Harsono, Ari (Journal of Socio-Cultural Sustainability and Resilience, 2025)
Background: This article discusses the attempt to establish hegemony in the 2024 presidential election through the presidential candidate debates. The presidential election is an important event in the transition of government in a democratic country. Presidential candidate debates are often seen merely as a campaign stage, but few view them as a medium for establishing hegemony, or as a marketplace where the identity products of presidential candidates are traded for voter loyalty. This study aims to explain how hegemony is established through the 2024 presidential candidate debates and how the identities of each candidate pair are traded for voter loyalty. Methods: This research was conducted by applying the theoretical framework of the “market for loyalties” as a method of analyzing the buying and selling of political products through the media. This study employs qualitative critical discourse analysis using the “market for loyalties” framework with data from debates, regulations, media, and campaign materials to examine identity construction and hegemony. Findings: This article indicate that hegemony is established through the ideologies and narratives brought by each candidate pair and their coalitions. The government plays a role in limiting the public's perspective on ideologies to only three presidential candidate pairs through presidential debates broadcast via mass media and digital media. These ideologies are reflected in the identities of each candidate pair; candidate pair 01 represents religious identity and change; 02 represents youth identity, loyalty to Jokowi, and continuity; 03 represents the identity of the PDIP (Partai Demokrasi Indonesia Perjuangan) as the ruling party and incumbent. Conclusion: This study concludes that the 2024 presidential candidate debates function as a medium for constructing hegemony through the articulation of ideologies and identities exchanged for voter loyalty. Novelty/Originality of this article: This article lies in applying the “market for loyalties” framework to analyze presidential debates as arenas of hegemony formation rather than merely campaign platforms.